Patients' Experience of PET-CT Scan at Armed Forces Institute of Radiology and Imaging Rawalpindi - Bilal, Rizwan; Ahmad, Mudassar; Slehria, Atiq ur Rehman; Mehdi, Syed Ali; Bilal, Muhammad; Jamal, Ali (Pakistan Armed Forces Medical Journal, 2022)
Objective: To evaluate the patients' feedback for potential improvements in the patient management of PET-CT Department.Study Design: Cross-sectional survey.Place and Duration of Study: Armed Forces Institute of Radiology and Imaging, Rawalpindi Pakistan, from Sep to Dec 2020.Methodology: A total of 350 participants were investigated in the study. Structured proforma was utilized for collecting patient feedback, and the ages ranged from 4 to 89 years. The collected data were arranged systematically to apply statistical tests using Microsoft excel.Results: Explicitly, 14(4%) patients communicated their reservations about further development in PET-CT scan practice. In this regard, 4(1.14%) patients suggested overall improvement in the department. Further, 4(1.14%) and 3(0.86%) patientss’ suggestions were towards staff behaviour and building of the department, respectively. Additionally, 2(0.57%) patients were not contented with the available prerequisite equipment, and 1(0.29%) patient suggested a reduction in scanning charges.Conclusion: More than 95% patients were satisfied with their experience. The studied data can be utilized to establish patient management protocols for similar PET-CT departments.